Scamocellular broncogenic carcinoma with pericardial involvement as the only distance metastasis - Paez-Codeso, Francisco M. (2021)
Squamous cell carcinoma of the lung causes distant metastases, rarely to the heart, causing pericardial effusion with evolution to cardiac tamponade and even death. We present the case of a middle-aged man who came to the emergency room due to chest pain with an incidental finding of a lesion at the level of the right lower lobe (LID) on the chest X-ray, during his study a single cardiac metastasis was observed as the only one Clinical manifestation of pericardial effusion without hemodynamic affectation, pharmacological treatment was started due to the diagnosis of squamous cell carcinoma, known before the appearance of the effusion, and he was referred to Oncology for chemotherapy treatment with improvement of the same without the need for invasive techniques such as pericardiocentesis or pericardiectomy. With this case, we observe the rarity of the pericardial effusion caused by the only metastasis of the patient from a lung carcinoma and its evolution without invasive treatments.